Gonadal tumor risk in pediatric and adolescent phenotypic females with disorders of sex development and Y chromosomal constitution with different genetic etiologies - Lu, Liangsheng; Luo, Feihong; Wang, Xiang (Frontiers in Pediatrics, 2022)
Objectives This retrospective study sought to investigate the risk and proportion of gonadal neoplasms in phenotypic female pediatric patients with DSD and the presence of the Y chromosome and different genetic backgrounds in a single Chinese center. Materials and Methods From January 2012 to December 2020, pediatric and adolescent patients with DSD and the presence of the Y chromosome who had unambiguous female genitalia and underwent bilateral gonadectomy or gonadal biopsy were included in this study. Patients’ demographics, karyotype, laboratory test results, gross pathology, and histology of gonadal tissue were all collected. The patients were divided into three groups based on their different genetic backgrounds, and the percentage of gonadal tumors was calculated to assess the risk of gonadal tumor and malignancy by etiology. Results A total of 22 patients with DSD and an unambiguous female phenotype with a Y chromosome were recruited. The mean age was 10.91 ± 4.99 years (9 months to 19 years). Gonadal neoplasia was confirmed in six (27.3%) cases by pathological examination of surgical gonadal tissue samples. Among 44 gonadal samples from these 22 patients, the following were identified: five gonadoblastomas, three dysgerminomas, and two Leydig cell tumors. The youngest patient with a tumor was a 2-year-old girl with 46,XY complete gonadal dysgenesis (46,XY CGD or Swyer syndrome) and bilateral gonadoblastoma. Patients with 46,XY complete gonadal dysgenesis (4/6; 66.7%) had the highest tumor occurrence rate. Among 10 patients with Turner syndrome with the presence of the Y chromosome, only one patient was diagnosed with a gonadal tumor. Leydig cell tumor was diagnosed in only one of six patients with 46,XY androgen synthesis/action disorders. Conclusion Pediatric patients with 46,XY complete gonadal dysgenesis had a significantly increased risk of developing gonadal tumors and underwent prophylactic gonadectomy as soon as the diagnosis was confirmed, whereas those with Turner syndrome with Y chromosome and 46,XY androgen synthesis/action disorders had a relatively low risk. In view of the limited number of patients, a large multicenter study with close follow-ups is needed to support these conclusions.